VALIDATION OF A TAILORED L2 MOTIVATIONAL SELF SYSTEM QUESTIONNAIRE THROUGH CONFIRMATORY FACTOR ANALYSIS - Saeed Safdari (Informascope, 2017)
This study investigated the structure of a self-report motivation questionnaire which was designed on the basis of the most recent theory of second language (L2) motivation research devised by Zoltan Dörnyei; namely, L2 motivational self system (L2MSS). The data was collected through administering the questionnaire to a sample of 318 undergraduate students. The scores underwent confirmatory factor analysis (CFA). The results of the analyses demonstrated that the hypothesized model is a good fit for the data and the questionnaire is both valid and reliable as a measure of motivational attributes.